Evaluating the Effectiveness of Quantitative Easing Measures of the Federal Reserve and the European Central Bank - Mulaahmetovic, Inda (Asian Economic and Financial Review, 2022)
This scientific paper examined the relation between conventional and unconventional monetary policy, with an anticipation to provide a comprehensive assessment of how they behave with the goal of mitigating financial distress, at the state level, influencing global economy. The sampling frame involved five variables related to the US Federal Reserve and five variables related to the European Central Bank, observed during the period 2015-2020 (data for January, April, July and October of each year, regarding every research variable were collected). These variables included: Euro Area Inflation Rate, ECB Bonds Yields, Euro Area Broad Money Supply (M2), Euro Area Unemployment Rate, Debt to GDP; and US Inflation Rate, US Treasury Yields, US Broad Money Supply (M2), US Unemployment Rate, Debt to GDP. Accordingly, two adequate research models were created. Research methodology focused on examining the accuracy of the hypotheses using SmartPLS 3 as a tool for conducting mediation analysis. Research implications suggest that Quantitative Easing caused a significant increase in the Federal Reserve’s and European Central Bank’s balance sheet, especially during the global financial crisis (2007-2008) and during the post-crisis, recovery period. In terms of policy recommendations, monetary authorities need to have policy sets ready in place, in order to know how to behave during and post an economic crisis. This scientific paper will serve as an accurate source of information to future researchers in the field of conventional and unconventional monetary measures, because the work is well systematically organized, clear for interpretation and provides an extensive insight into the Fed’s and ECB’s transmission mechanisms of monetary policy.